A seat-level nowcast of the Front National in the 2017 legislatives. Issue 4 (December 2016) - Evans, Jocelyn; Ivaldi, Gilles
Abstract We look to forecast the number of seats the Front National (FN) will win in the 2017 legislative election. We use the most recent subnational ballot, the 2015 regional election, to estimate support for the party, and model reallocation of first-round legislative votes in the second round by applying the pattern seen between the 2011 cantonal and 2012 legislative elections. Using different levels of turnout and four different scenarios of Left-bloc coalition arrangements, both of which strongly influence how the FN performs in run-off ballots, we estimate that a likely, but conservative, scenario would result in 29 FN seats, if a similar pattern to 2011–2012 obtains. This number of seats would allow the FN to form a Parliamentary group in the National Assembly.